Forum: Exchanges on Cases and Policy Courses - Greenwood, William T. (Academy of Management Journal, 1967)
The article presents a rejoinder by William T. Greenwood in response to comments made about his December 1966 article regarding business policy. The author discusses the definition of business poli...